2020
DOI: 10.3390/ijms21051812
|View full text |Cite
|
Sign up to set email alerts
|

Global Characterization of GH10 Family Xylanase Genes in Rhizoctonia cerealis and Functional Analysis of Xylanase RcXYN1 During Fungus Infection in Wheat

Abstract: Wheat (Triticum aestivum L.) is an important staple crop. Rhizoctonia cerealis is the causal agent of diseases that are devastating to cereal crops, including wheat. Xylanases play an important role in pathogenic infection, but little is known about xylanases in R. cerealis. Herein, we identified nine xylanase-encoding genes from the R. cerealis genome, named RcXYN1–RcXYN9, examined their expression patterns, and investigated the pathogenicity role of RcXYN1. RcXYN1–RcXYN9 proteins contain two conserved glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
13
0
1
Order By: Relevance
“…In other phytopathogenic fungi, several M36 metalloproteases have been evidenced to be important virulence factors or effectors [27][28][29][30]32,33]. Our previous studies showed that the R. cerealis cutinase RcCUT1 and the R. cerealis xylanase RcXYN1 could trigger plant cell death and H 2 O 2 accumulation, and upregulated transcriptions of several defense-related genes in protein-treated wheat plants, leading to enhanced disease [11,12]. Here, sequence analysis showed RcMEP2 might be a secreted protein.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In other phytopathogenic fungi, several M36 metalloproteases have been evidenced to be important virulence factors or effectors [27][28][29][30]32,33]. Our previous studies showed that the R. cerealis cutinase RcCUT1 and the R. cerealis xylanase RcXYN1 could trigger plant cell death and H 2 O 2 accumulation, and upregulated transcriptions of several defense-related genes in protein-treated wheat plants, leading to enhanced disease [11,12]. Here, sequence analysis showed RcMEP2 might be a secreted protein.…”
Section: Discussionmentioning
confidence: 71%
“…Using the purified RcMEP2 protein infiltrated into wheat and N. benthamiana leaves, our results reveal that the RcMEP2 is capable of inducing cell death and triggering H 2 O 2 rapidly-excessive accumulation in the treated leaves. Unlike the induction effect of the cutinase RcCUT1 and xylanase RcXYN1 of R. cerealis on transcriptions of several defense-related genes in these protein-treated wheat plants [11,12], RcMEP2 did not upregulate the transcriptions of these host defense-related genes and repressed the expression of wheat chitinases, implying distinct mechanisms underlying the roles of RcMEP2, RcCUT1, and RcXYN1. As expected, RcMEP2 treatment significantly increased disease severity compared to the negative controls, indicating that RcMEP2 treatment enhances virulence of R. cerealis during the fungal infection to wheat.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations